2022
DOI: 10.3390/foods11111626
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fibril Entanglement on Pickering Emulsions Stabilized by Whey Protein Fibrils for Nobiletin Delivery

Abstract: The aim of the study was to investigate the effects of whey protein isolate (WPI) fibrils entanglement on the stability and loading capacity of WPI fibrils-stabilized Pickering emulsion. The results of rheology and small-angle X-ray scattering (SAXS) showed the overlap concentration (C*) of WPI fibrils was around 0.5 wt.%. When the concentration was higher than C*, the fibrils became compact and entangled in solution due to a small cross-sectional radius of gyration value (1.18 nm). The interfacial behavior wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…At the final stage, the interfacial pressure of the 0.5% MDG sample was increased, and the maximum value of the interfacial pressure was 18.78 mN/m for the 0.1% PPI–0.5% MDG. The gradual increase in E with the adsorption time was explained by an intermolecular interaction and protein adsorptions at the interface [ 28 , 29 ]. The result showed that MDG addition played a dominant part in the interfacial tension, and its potential mechanism on the interfacial film was further analyzed from the nonlinear rheology.…”
Section: Resultsmentioning
confidence: 99%
“…At the final stage, the interfacial pressure of the 0.5% MDG sample was increased, and the maximum value of the interfacial pressure was 18.78 mN/m for the 0.1% PPI–0.5% MDG. The gradual increase in E with the adsorption time was explained by an intermolecular interaction and protein adsorptions at the interface [ 28 , 29 ]. The result showed that MDG addition played a dominant part in the interfacial tension, and its potential mechanism on the interfacial film was further analyzed from the nonlinear rheology.…”
Section: Resultsmentioning
confidence: 99%
“…To some extent, microorganisms and humans have coevolved, and the symbiosis and interactions promote the development of the host and microbes by forming a strong immune system in the host [49]. The complex dialog between the host and the microbiota ensures peaceful coexistence with the bene cial ingredients in the diet and protects against potential harmful pathogens [50,51]. The relationship between ECD and lipid metabolism is achieved through the interaction between the liver, intestine and gut microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…When di reached the end point (120 min), the FFA release rate of the emulsion was 32.7%, was almost three times that of the control group (11.1%), revealing that the forma the emulsion remarkably accelerated lipid digestion. This was mainly because phase in the Pickering emulsion was dispersed in droplets, which promoted the of enzymes with the oil [17]. The bioaccessibility of quercetin was characterized by determining the amo quercetin in the micelles at the end of digestion.…”
Section: Lipid Digestion and Bioaccessibility Of Quercetinmentioning
confidence: 99%
“…Compared with the native protein, the viscosity, gel property and emulsifying ability of whey protein isolate fibril (WPIF) are remarkably improved [ 15 , 16 ]. And WPIF has been applied as a stabilizer of Pickering emulsions to deliver bioactive substances [ 17 ]. Therefore, it is worth exploring the feasibility of constructing stable hordein/WPIF complex-stabilized O/W Pickering emulsion.…”
Section: Introductionmentioning
confidence: 99%